Treatment With 2-BFI Attenuated Spinal Cord Injury by Inhibiting Oxidative Stress and Neuronal Apoptosis via the Nrf2 Signaling Pathway - Lin, Xiaolong; Zhu, Jie; Ni, Haibo; Rui, Qin; Sha, Weiping; Yang, Huilin; Li, Di; Chen, Gang (Frontiers in Cellular Neuroscience, 2019)
Previous reports showed that 2-(-2-benzofuranyl)-2-imidazoline (2-BFI) has antioxidant, anti-inflammatory and antiapoptotic effects on neuroprotection in numerous disorders. However, the precise mechanisms were remains elusive. The nuclear factor c factor 2 (Nrf2)/antioxidant response element (ARE) signalling pathway plays an important and essential role in the antioxidant and anti-inflammatory responses of the cell. Therefore, the purpose of this study was to investigate the potential neuroprotective effects of 2-BFI in a rat model of spinal cord injury (SCI) and to determine whether its neuroprotective effects are associated with the activation of Nrf2. To test this hypothesis, we examined the potential roles of 2-BFI in SCI models which were established in rats using a clip-compression injury method. Our results showed that treatment with 2-BFI twice daily improved locomotion recovery from SCI, which increased Nrf2 expression in both neurons and astrocytes, meanwhile, the level of haeme oxygenase-1 (HO-1) also significantly enhanced. In addition, after the treatment with 2-BFI increased levels of superoxidase dismutase (SOD) and glutathione peroxidase (GPx) indicated the antioxidant effect of the drug. Furthermore, the upregulation of Bcl-2 and downregulation of Bax and caspase-3 implied antiapoptotic effects on neuroprotection of 2-BFI, which were verified by the Fluoro-Jade B (FJB) staining and TUNEL staining. Collectively, these results add to a growing body of evidence supporting that 2-BFI may attenuate SCI mediated by activation of the Nrf2/HO-1 signalling pathway.